Relationship Between Financial and Economic Evaluations for Different Types of Project - World Bank (Washington, DC, 2012)
Appraisal can be undertaken from different perspectives, depending on the objectives of the commissioning body. The key choices are: Business case - requires a commercial perspective; and, Appraisal for Government - usually considers both the social perspective, and the fiscal perspective. A commercial or financial appraisal focuses on the gains and losses to one organization, typically a firm or an agency of government. Social appraisal is the broadest, and can be used to show how the (narrower) appraisals for business, government and citizens aggregate up to the social level. The fiscal perspective focuses on the project's impacts on government expenditure and receipts. It can be thought of as a commercial appraisal from the perspective of Government. The items in a financial appraisal are money flows to, and from the organization concerned. In contrast to the social cost-benefit analysis, external costs and benefits are omitted. The principle of 'comprehensiveness' does not apply; it is replaced by a commercial focus on matters which concern the organization itself, and not the wider world.